1983
DOI: 10.3758/bf03198285
|View full text |Cite
|
Sign up to set email alerts
|

Pupil dilations following pairs of identical and related to-be-remembered words

Abstract: Two experiments are reported in which the spacing between pairs of identical (Experiment 1) or pairs of related (Experiment 2) to-be-remembered words were varied while pupil diameter and frequency judgments were measured. In Experiment I, frequency judgments increased with increases in spacing length. In Experiment 2, frequency judgments decreased with increases in spacing length. In both experiments, however, pupil dilations increased with increases in spacing length. These results are interpreted as supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…Moreover, using pupillary deconvolution techniques [37], [38], it should be possible to deduce proficiency levels from pupil dilations in more typical memory paradigms that are characterized by a faster pace. Interestingly, these results corroborate findings by Magliero [55] who observed effects of recency on pupil dilation when varying the time between repetitions of items in a list that had to be committed to memory. When items were presented for a second time, he found that repetitions that followed the initial presentation at shorter lags (i.e., with 0 or 1 intervening trials) resulted in smaller task-evoked pupillary responses than repetitions at longer lags (i.e., with 4 or 8 intervening trials), providing a link between the retrieval processes reported in this study, and the encoding processes studied by Magliero.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, using pupillary deconvolution techniques [37], [38], it should be possible to deduce proficiency levels from pupil dilations in more typical memory paradigms that are characterized by a faster pace. Interestingly, these results corroborate findings by Magliero [55] who observed effects of recency on pupil dilation when varying the time between repetitions of items in a list that had to be committed to memory. When items were presented for a second time, he found that repetitions that followed the initial presentation at shorter lags (i.e., with 0 or 1 intervening trials) resulted in smaller task-evoked pupillary responses than repetitions at longer lags (i.e., with 4 or 8 intervening trials), providing a link between the retrieval processes reported in this study, and the encoding processes studied by Magliero.…”
Section: Discussionsupporting
confidence: 89%
“…Those who reported having paid more attention tended to have learned more from the text. These findings dovetail nicely with those of Magliero (1983) who found that pupil size associated with the second of two repeated items increases as the spacing between presentations increases. Since pupil size is a well-accepted measure of attention and is known to vary directly with amount of processing, this finding also suggests that differences in attention underlie at least some spacing effects.…”
Section: Deficient-processing Theoriescontrasting
confidence: 45%
“…Recall that distributed reviews and tests have been found to be more "attention-grabbing" than similar massed events (e.g., Dempster, 1986;Magliero, 1983;Zechmeister and Shaughnessy, 1980). Thus, spaced repetitions are likely to promote student time-on-task, a highly valued classroom behavior.…”
Section: Educational Implicationsmentioning
confidence: 99%
“…Dellarosa & Bourne, 1985;Greene, 1989). For example, measurements of pupil dilation indicate that people pay more attention on the second of two spaced learning opportunities than they do on the second of two massed learning opportunities (Magliero, 1983). Also, people are more accurate in a secondary detection task when they are studying the second presentation of a massed item than when they are studying the second presentation of a spaced item (i.e.…”
Section: Explanations Of the Spacing Effectmentioning
confidence: 99%